A IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DALAM UPAYA PENINGKATAN MUTU PEMBELAJARAN MATA PELAJARAN AKIDAH AKHLAK - IPING HANAFI (UNISAN JURNAL, 2024)
This research uses data collection techniques using interview methods, observation methods and documentation methods. The data validity technique in this research is data collection triangulation. Qualitative data analysis in this research is descriptive data which consists of three activities that take place simultaneously, namely data reduction, data presentation and conclusion drawingMadrasah-Based Management (MBM) is essentially a recognition that the educational process will not run well if everything is controlled from the center. The educational process is not a factory where once a button is pressed, the process will run regularly as programmed. Because, education is a process that involves interactions between various existing inputs and output interactions with the environment. The aim of this research is to determine the implementation of Madrasah-Based Management (MBM) in improving moral education. The data sources used in this research are primary and secondary data sources.